Prediction of present and future distribution areas of Juniperus drupacea Labill and determination of ethnobotany properties in Antalya Province, Türkiye - Turkmenoglu, Guliz; Sarikaya, Ayse Gul; Uzun, Almira; Fakir, Huseyin (De Gruyter Poland Sp Z O O, 2024)
Ethnobotanical studies revealed the experience and knowledge of people who learned the therapeutic virtues of plants through trials and errors and transferred their knowledge to the next generations. This study determined the ethnobotanical use of Juniperus drupacea (Andiz) in the Antalya province and the current and future potential distribution areas of J. drupacea in T & uuml;rkiye during 2041-2060 and 2081-2100 according to the SSP2-4.5 and SSP5-8.5 scenarios and based on the IPSL-CM6A-LR climate change model. The very suitable areas encompassed 22379.7 km(2). However, when the SSP2-4.5 scenario was considered, the areas most suitable for J. drupacea comprised 6215.892 km(2) for 2041-2060 and 378.318 km(2) for 2081-2100. Based on the SSP5-8.5 scenario, the area most suitable for J. drupacea was 979.082 km(2) for 2041-2060. However, no suitable areas were identified with the SSP5-8.5 scenario for 2081-2100. Considering the models for the future estimated distribution areas of J. drupacea, serious contractions endangering the species are predicted in its distribution areas. Therefore, scientific research should focus on identifying J. drupacea populations and genotypes that demonstrate resilience to future drought conditions resulting from climate change. This endeavor is crucial as it holds significant ecological and economic values.
Keywords: Andiz (Juniperus drupacea); Andiz molasses; climate change; ethnobotany; maximum entropy